2011
DOI: 10.1242/dev.066951
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mouse embryonic stem cell self-renewal by a Yes–YAP–TEAD2 signaling pathway downstream of LIF

Abstract: SummaryThe cytoplasmic tyrosine kinase Yes has previously been shown to have an important role in maintaining mouse and human embryonic stem (ES) self-renewal through an unknown pathway downstream of leukemia inhibitory factor (LIF) and one or more factors in serum. Here, we show that TEAD2 and its transcriptional co-activator, the Yes-associated protein YAP, co-operate in a signaling pathway downstream of Yes. We show that YAP, TEAD2 and Yes are highly expressed in self-renewing ES cells, are activated by LIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
3

Year Published

2012
2012
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 23 publications
1
35
3
Order By: Relevance
“…However, the mechanism responsible for specificity of YAP and TAZ in BMP and TGFbeta signaling is not known. Another report suggests the regulation of YAP by LIF, which is required by mouse but not human ESCs, which is another possible explanation for the role of YAP and TAZ in the self-renewal of human and mouse ESCs (Tamm et al, 2011).…”
Section: The Hippo Pathway Regulates Es Cell Self-renewal and Ips Celmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the mechanism responsible for specificity of YAP and TAZ in BMP and TGFbeta signaling is not known. Another report suggests the regulation of YAP by LIF, which is required by mouse but not human ESCs, which is another possible explanation for the role of YAP and TAZ in the self-renewal of human and mouse ESCs (Tamm et al, 2011).…”
Section: The Hippo Pathway Regulates Es Cell Self-renewal and Ips Celmentioning
confidence: 99%
“…However, only until recently, it was demonstrated that YAP as well as its transcription factor partner TEAD promotes ES cell self-renewal. When mouse ESCs were induced to differentiate, YAP was inactivated as indicated by decreased protein level and increased phosphorylation (Lian et al, 2010;Tamm et al, 2011). However, YAP overexpression prevents mouse ESCs from differentiation even under differentiation condition such as leukemia inhibitory factor (LIF) withdrawal (Lian et al, 2010;Tamm et al, 2011).…”
Section: The Hippo Pathway Regulates Es Cell Self-renewal and Ips Celmentioning
confidence: 99%
See 3 more Smart Citations